Potential Role of Biofilm Formation in the Development of Digestive Tract Cancer With Special Reference to Helicobacter pylori Infection - Rizzato, Cosmeri; Torres, Javier; Kasamatsu, Elena; Camorlinga-Ponce, Margarita; Bravo, Maria Mercedes; Canzian, Federico; Kato, Ikuko (Frontiers in Microbiology, 2019)
Bacteria are highly social organisms that communicate via signaling molecules and can assume a multicellular lifestyle to build biofilm communities. Until recently, complications from biofilm-associated infection have been primarily ascribed to increased bacterial resistance to antibiotics and host immune evasion, leading to persistent infection. In this theory and hypothesis article we present a relatively new argument that biofilm formation has potential etiological role in the development of digestive tract cancer. First, we summarize recent new findings suggesting the potential link between bacterial biofilm and various types of cancer to build the foundation of our hypothesis. To date, evidence has been particularly convincing for colorectal cancer and its precursor, i.e. polyps, pointing to several key individual bacterial species, such as Bacteroides fragilis, Fusobacterium nucleatum and Streptococcus gallolyticus subsp. Gallolyticus. Then, we further extend this hypothesis to one of the most common bacterial infection in humans, Helicobacter pylori (Hp), which is considered a major cause of gastric cancer. Thus far, there has been no direct evidence linking in vivo Hp gastric biofilm formation to gastric carcinogenesis. Yet, we synthesize the information to support an argument that biofilm associated-Hp is potentially more carcinogenic, summarizing biological characteristics of biofilm-associated bacteria. We also discuss mechanistic pathways as to how Hp or other biofilm-associated bacteria control biofilm formation and highlight recent findings on Hp genes that influence biofilm formation, which may lead to strain variability in biofilm formation. This knowledge may open a possibility of developing targeted intervention. We conclude, however, that this field is still in its infancy. To test the hypothesis rigorously and to link it ultimately to gastric pathologies (e.g., premalignant lesions and cancer), studies are needed to learn more about Hp biofilms, such as compositions and biological properties of extracellular polymeric substance, presence of non-Hp microbiome and geographical distribution of biofilms in relation to gastric gland types and structures. Identification of specific Hp strains with enhanced biofilm formation would be helpful not only for screening patients at high risk for sequelae from Hp infection, but also for development of new antibiotics to avoid resistance, regardless of its association with gastric cancer.